The Regulation of the Death Penalty in Relation to Legal Certainty and Human Rights - Pramesti, Ni Putu Diah Indira; Darmadi, Anak Agung Ngurah Oka Yudistira (International Journal of Business, Law, and Education, 2026)
This study examines the ambiguity of legal norms governing the death penalty under Law No. 1 of 2023 concerning the Criminal Code and its implications for legal certainty and human rights protection. This research employs a normative legal method using statutory, conceptual, and historical approaches through library-based legal research. The findings reveal several normative ambiguities, particularly regarding the criteria for imposing the death penalty, the assessment of “commendable attitude and conduct,” the mechanism of Presidential Decrees, and the procedures for execution. These ambiguities may give rise to legal uncertainty, inconsistent judicial decisions, and excessive discretion among law enforcement authorities. From a human rights perspective, such ambiguities also create uncertainty regarding the legal status of death-row convicts and may potentially violate the principle of due process of law. Therefore, clearer, more precise, and more operational legal provisions are required to ensure that the regulation of the death penalty under the 2023 Criminal Code guarantees legal certainty while remaining consistent with human rights principles.